2022
DOI: 10.3389/fnbeh.2022.827673
|View full text |Cite
|
Sign up to set email alerts
|

Facing Your Fear in Immersive Virtual Reality: Avoidance Behavior in Specific Phobia

Abstract: Specific phobias are the most common anxiety disorder and are characterized by avoidance behavior. Avoidance behavior impacts daily function and is proposed to impair extinction learning. However, despite its prevalence, its objective assessment remains a challenge. To this end, we developed a fully automated experimental procedure using immersive virtual reality. The procedure contained a behavioral search, forced-choice, and an approach task with varying degrees of freedom and task relevance of the stimuli. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 63 publications
0
0
0
Order By: Relevance
“…The effectiveness of iVRET in addressing disgust, particularly within the context of contamination fears, has been analyzed in several studies on both healthy [25][26][27][28][29] and clinical populations [17][18][19][20][21][22][23][24]. Among the studies conducted on healthy populations, investigations by Inozu et al [25,26] stand out, demonstrating VRET's potential to significantly reduce contamination fear, disgust, and hand-washing urges; in particular, we found large effects size (see Table 2) for iVRET effectiveness on disgust outcomes in the experimental group compared to controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effectiveness of iVRET in addressing disgust, particularly within the context of contamination fears, has been analyzed in several studies on both healthy [25][26][27][28][29] and clinical populations [17][18][19][20][21][22][23][24]. Among the studies conducted on healthy populations, investigations by Inozu et al [25,26] stand out, demonstrating VRET's potential to significantly reduce contamination fear, disgust, and hand-washing urges; in particular, we found large effects size (see Table 2) for iVRET effectiveness on disgust outcomes in the experimental group compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…From automated immersive experiences to the application of tactile and haptic feedback, the selected studies represent the forefront of technology-assisted therapy in managing SP. Binder et al [18] highlights significant avoidance behavior in individuals with SP when exposed to virtual simulations of spiders. Through iVR tasks designed to measure avoidance, such as "Fishing" (a behavioral search task), "Path-Choice" (a forced-choice task), and "Touch the Enemy" (a behavioral approach task), the study observed that phobic participants exhibited pronounced avoidance behaviors and physiological responses indicative of negative emotions (i.e., fear and disgust).…”
Section: Specific Phobias (Sp)mentioning
confidence: 99%
See 1 more Smart Citation
“…2022 [74] Researchers developed a fully automated experimental procedure using immersive VR involving behavioral search, forced-choice and an approaching task with varying degrees of freedom and stimulus relevance. In this study, scientists examined the sensitivity and feasibility of these tasks to assess avoidance behavior in patients with specific phobias.…”
Section: Binder Et Almentioning
confidence: 99%
“…Table 1 presents and indicates examples of neuroscientific areas of using virtual environments and tools, including pain management [31,[56][57][58], improvement of brain injury patients [5,26,[59][60][61], post-stroke [10,20,25,33,[65][66][67], prevention, and diagnosis and therapy of many serious illnesses. Examples include diseases such as neurodevelopmental disorders (e.g., attentiondeficit hyperactivity disorder, ADHD [22,80,81]); schizophrenia spectrum disorders (e.g., schizophrenia [82,83]); autism spectrum disorders (e.g., autism [84,85]); mood (e.g., depressive disorders [86,87]), anxiety (e.g., panic and phobias [74][75][76]), trauma-and stressorrelated (e.g., post-traumatic stress disorder, PTSD [73]), neurocognitive (e.g., Parkinson's or Alzheimer's and memory cognitive impairment diseases [23,24,47,[69][70][71][72][77][78][79]) and neuromuscular disorders (e.g., multiple sclerosis [32,[62][63]…”
Section: Hinze Et Al 2021 [76]mentioning
confidence: 99%